The Effect of Knowledge, Motivation, Marketing Ease Expectation, and Income Expectation on Interest of Hydroponic Vegetable Entrepreneurship in the Region - Winarno, Retmono Agung (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to discover the knowledge, motivation, marketing ease expectation, and income expectation of the interest in hydroponic vegetable entrepreneurship. The development of hydroponic agriculture as a land utilization measure requires direction and the support of knowledge about hydroponics. This method used was quantitative with questionnaires on the studied variables. In this study, researchers took 114 respondents in Deli Serdang Regency, North Sumatra Province. The analysis of this study used a structural Equation Model (SEM) approach with the help of smart PLS. The results explained that interest in hydroponic entrepreneurship is influenced by marketing ease expectations, income expectations, motivation, and knowledge.